Hubungan Antara Kronotipe Dengan Bmi(Body Mass Index) Pada Siswa Sma Negeri 4 Surakarta - Dewantari, Sukma; , dr. Yusuf Alam Romadhon, M.Kes (2017)
Prevalence of overweight and obesity has increased in the past three decades with the number of children who are overweight increased threefold. All this time, overweight is believed to occur as a result of energy intake (food and beverage consumption) is greater than the expenditure of energy (through metabolism and physical activity), genetic and environmental factors, but some recent research suggests that there is a correlation between chronotype and Body Mass Index. To prove the correlation between chronotype and BMI (Body Mass Index) in SMA Negeri 4 Surakarta. Analytic observational study with cross sectional approach and cluster sampling technique sampling. Chronotype measured used Morningness-Eveningness Questionnaire (MEQ) and the classification of BMI used CDC percentile table. Pearson Test data analysis used SPSS version 23. Obtained values of r = -0.274 and p = 0.018. There is an inverse relationship between chronotype and BMI. There is an inverse correlation between chronotype and BMI. When the value of chronotype is higher, it makes the BMI scores become lower. Or in other words, when the chronotype getting earlier (morningness type), it makes BMI scores become lower.